2020
DOI: 10.1158/1538-7445.sabcs19-pd5-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD5-03: Relationship between tumor-infiltrating lymphocytes (TILs) and outcomes in the KEYNOTE-119 study of pembrolizumab vs chemotherapy for previously treated metastatic triple-negative breast cancer (mTNBC)

Abstract: Background: Several studies show that the presence of TILs has prognostic significance in TNBC, with greater lymphocytic infiltration associated with clinical outcomes. In the phase 2 KEYNOTE-086 study, TIL levels were a surrogate marker of preexisting antitumor immunity and were independent predictors of response to pembrolizumab (pembro) monotherapy. Here, we analyzed the relationship between the presence of TILs and outcomes in the phase 3 KEYNOTE-119 (NCT02555657) study of pembro monotherapy vs single-agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 0 publications
7
35
0
Order By: Relevance
“…In addition, the presence and density of pre-treatment and on-treatment stromal TILs were significantly associated with pCR in a cohort of the KEYNOTE-173 trial, which assessed the benefit of pembrolizumab added to NAC 156 . Similar results have been showed in exploratory biomarker analysis of the IMpassion130 157 and KEYNOTE-119 trials 158 . Interestingly, the latter study showed that high TILs predicted favorable clinical outcomes in patients with metastatic TNBC treated with pembrolizumab, but not with chemotherapy, reinforcing the predictive value of this biomarker.…”
Section: Introductionsupporting
confidence: 85%
“…In addition, the presence and density of pre-treatment and on-treatment stromal TILs were significantly associated with pCR in a cohort of the KEYNOTE-173 trial, which assessed the benefit of pembrolizumab added to NAC 156 . Similar results have been showed in exploratory biomarker analysis of the IMpassion130 157 and KEYNOTE-119 trials 158 . Interestingly, the latter study showed that high TILs predicted favorable clinical outcomes in patients with metastatic TNBC treated with pembrolizumab, but not with chemotherapy, reinforcing the predictive value of this biomarker.…”
Section: Introductionsupporting
confidence: 85%
“…Higher levels of TILs have also been associated with better responses to ICI monotherapy, 80 and recently TILs $5% have been shown to independently predict improved response and survival following pembrolizumab but not chemotherapy in the KEYNOTE-119 trial of pembrolizumab compared with chemotherapy monotherapy in patients with mTNBC treated with 1 to 2 lines of prior systemic therapy, although these results are preliminary and used a one-sided P value for pembrolizumab. 81,82 Similarly, a study of neoadjuvant durvalumab concurrent with nab-paclitaxel and dosedense doxorubicin and cyclophosphamide in 57 patients with early-stage TNBC found that high CD8 cell density and immune gene expression signatures, as well as DNA damage response signatures, correlated with higher pCR rates, 83 although these changes were not shown to be specific to ICI therapy compared with chemotherapy alone. Finally, the TONIC trial (NCT02499367) of various induction regimens prior to single-agent nivolumab showed that tumors treated with doxorubicin or cisplatin demonstrated increased expression of genes related to the PD-L1 pathway, T-cell cytotoxicity, and inflammation, suggesting that certain chemotherapy agents induce favorable tumor immune microenvironment changes that promote response to PD-1 blockade.…”
Section: Biomarkers Of Immunotherapy Responsementioning
confidence: 99%
“…In the phase III KEYNOTE-119 trial, where single-agent pembrolizumab failed to improve OS as compared to chemotherapy per the physician’s choice in 622 pre-treated patients with advanced TNBC [ 88 ], strTILs as both continuous and categorical variables (cutoff 5%) were significantly associated with all clinical outcomes (best overall response—BOR, ORR, disease control rate—DCR, OS and PFS) only in the immunotherapy arm, thus suggesting a potential predictive role of TILs in predicting pembrolizumab benefit in heavily pre-treated advanced TNBC patients [ 89 ].…”
Section: Adaptive Immunitymentioning
confidence: 99%